Prenatal diagnosis of β-thalassemia/Hb E by hemoglobin typing compared to DNA analysis - Sirichotiyakul S. (2014)
To determine the accuracy of prenatal diagnosis of β-thalassemia (β-thal)/Hb E disease using fetal hemoglobin (Hb) typing compared to DNA analysis, automated DNA sequencing was performed on 98 blood samples from fetuses diagnosed as β-thal/Hb E by Hb typing. Thirteen samples from homozygous Hb E fetuses were also collected. The Hb patterns obtained by high performance liquid chromatography (HPLC) from both groups were analyzed. The codon 26 (G>A) mutation was identified in all 98 samples. The β-globin gene mutation was identified in 97 cases by DNA sequencing and the 3.4 kb deletion by polymerase chain reaction (PCR) in one case. The result from DNA analysis was in agreement with the HPLC result in all samples. In β-thal/Hb E fetuses, the Hb A level was 0-0.3% and mean Hb A2(E) level was 1.3 ± 0.3%. In homozygous Hb E fetuses, the Hb A level was 0% and mean Hb A2(E) level was 2.48 ± 0.6%. The Hb pattern obtained by HPLC on fetal blood is a reliable and accurate method for prenatal diagnosis of this disease. Copyright © Informa Healthcare USA, Inc.